Laboratory Biomarker Changes Following Extracorporeal Blood Oxygenation and Ozonation (EBOO): A Retrospective Eight-Patient Case Series - Abhinit Gupta (Journal of Complementary and Alternative Medical Research, 2026)
Background: Extracorporeal blood oxygenation and ozonation (EBOO) is an extracorporeal procedure involving oxygen-ozone exposure and blood filtration. Clinical evidence remains limited, and EBOO is investigational in many settings. Objective: To describe paired laboratory changes available before and after EBOO in eight adults treated during routine clinical care. Methods: This uncontrolled retrospective case series included eight heterogeneous patients with comparable pre- and post-procedure laboratory reports. Results: Triglycerides decreased in all six patients with paired values, LDL cholesterol decreased in all four, total cholesterol decreased in four of five, HDL increased in all three, non-HDL cholesterol decreased in all three, and VLDL decreased in both patients with paired measurements. hsCRP decreased in four of five patients but increased in one; CRP decreased in the single patient with paired CRP values. TSH decreased in Cases 1–3 but increased from 30.2 to 48.7 mIU/L in Case 4, where haemoglobin decreased from 11.4 to 10.3 g/dL. In Case 7, ALT increased from 41.8 to 151.4 U/L and fasting glucose from 110.1 to 135 mg/dL. Conclusion: These observations are uncontrolled temporal associations and do not establish efficacy, safety, treatment effect, or causality. Prospective controlled studies using standardised protocols, follow-up, and predefined safety monitoring are required.